BRAYO CRISPY CHIPS INNOVATIVE PRODUCT BASED ON LOCAL WISDOM IN SAYUNG TO SUPPORT LEARNING OF SOCIAL SCIENCE “THE USAGE OF NATURAL RESOURCES” FOR GRADE V - Sulianto, Joko; Anggun Setiawan; Suci Rahayu (Universitas PGRI Semarang, 2024)
Education is a crucial matter in shaping a nation’s future by fostering professional human resources equipped with knowledge and technology. This research explores the contributions of edupreneurship activities to children's development, focusing on fine motor skills, understanding basic economic concepts, and enhancing cognitive and social skills. Using a qualitative and participatory approach, this study involved 15 children at SD Negeri Purwosari 1 in hands-on activities related to the production of